2014 IEEE Aerospace Conference 2014
DOI: 10.1109/aero.2014.6836272
|View full text |Cite
|
Sign up to set email alerts
|

Formation establishment and reconfiguration using differential elements in J2-perturbed orbits

Abstract: A practical algorithm is developed for on-board plan ning ofn-impulse fuel-optimal maneuvers for establishment and reconfiguration of spacecraft formations. The method is valid in circular and elliptic orbits and includes first-order secular h effects. The dynamics are expressed in terms of differential mean orbital elements, and relations are provided to allow the formation designer to transform these into intuitive geometric quantities for visualization and analysis. The maneuver target ing problem is formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In their study [8], De Iuliis et al identified fuel-optimal low-thrust profiles capable of executing formation reconfiguration, utilizing an improved version of the well-known Legendre pseudospectral method. On the other hand, Roscoe et al [9] employed primer vector theory [10,11] to achieve impulsive orbital reconfiguration in the relative motion between two agents. Their method entails iteratively addressing the discrete fuel optimal guidance problem to match the optimal times of the continuous formulation.…”
Section: Introductionmentioning
confidence: 99%
“…In their study [8], De Iuliis et al identified fuel-optimal low-thrust profiles capable of executing formation reconfiguration, utilizing an improved version of the well-known Legendre pseudospectral method. On the other hand, Roscoe et al [9] employed primer vector theory [10,11] to achieve impulsive orbital reconfiguration in the relative motion between two agents. Their method entails iteratively addressing the discrete fuel optimal guidance problem to match the optimal times of the continuous formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Another aspect of formation control of small satellites is the prescription and planning of the needed formation maneuvers at di erent situations. Planning of n-impulse fuel-optimal maneuvers for establishment and recon guration of spacecraft formations are considered for circular and elliptic orbits [6]. Collision avoidance maneuvers for a swarm of satellites in formation, which return to their original con guration after a threat has passed, is considered in [7] using biological rules of avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of this work is to evaluate if and how much the station keeping logic could be beneficial for coordinated flight missions characterized by a different number of spacecraft and different distance boundaries. To study and implement the station keeping logic, it can be advantageous expressing the relative motion through relative orbital elements, since the orbital elements have a slow variation over time and corrections of specific elements with theoretically no effect on the others can be obtained using impulsive control (see e.g., [25,24,23,18,3,22,12]).…”
Section: Introductionmentioning
confidence: 99%